Estetika Tari Lenggok Karya Ida Sulistyarini dan Susiati di Kabupaten Banyumas - Laela Ajrin Dwi Saputri; Joko Wiyoso (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study aims to describe the aesthetics of the performance form of the Lenggok Dance created by Ida Sulistyarini and Susiati, which has developed in Banyumas Regency. The Lenggok Dance is a creative dance work rooted in the local Banyumasan tradition and presents distinctive movement characteristics along with regional cultural values. This research uses Djelantik’s aesthetic theory with a qualitative method and a phenomenological approach. Data collection techniques include observation, interviews, and documentation. Data validity techniques employ triangulation of sources, techniques, and time. Data analysis is carried out by examining the aesthetic elements of the dance, which include form, content or substance, and presentation or performance contained in the show. The results of the study indicate that the aesthetics of the Lenggok Dance are reflected through the harmony between dynamic and flexible lenggeran movements and the rhythmic Banyumasan musical accompaniment, as well as visual support from makeup and costumes that strengthen the character of the dance. In addition, the Lenggok Dance contains aesthetic values that represent the cultural identity of Banyumas, particularly in the processing of movements and expressions that reflect flexibility, joy, and local wisdom. This study is expected to contribute to the development of dance studies, especially related to the aesthetics of regional creative dance, and to serve as a reference for the preservation and development of Banyumasan performing arts.